Differential expression of the adult specifier E93 in the strepsipteran Xenos vesparum Rossi suggests a role in female neoteny - Chafino, S; López-Escardó, D; Benelli, G; Kovac, H; Casacuberta, E; Franch-Marro, X; Kathirithamby, J; Martín, D (Nature Publishing Group, 2018)
Holometaboly is a key evolutionary innovation that has facilitated the spectacular radiation of insects. Despite the undeniable advantage of complete metamorphosis, the female of some holometabolous species have lost the typical holometabolous development through neoteny. In Xenos vesparum Rossi (Strepsiptera: Stylopidae), a derived species of the holometabolous endoparasitic order Strepsiptera, neotenic females reach sexual maturity without the pupal and the imaginal stages, thus retaining their larval morphology (with the exception of the anterior part of the body or cephalothorax), while males undergo normal pupal-based metamorphosis. Expression of the “adult-specifier” E93 factor has been shown to be required for proper metamorphosis in holometabolous insects. Here, we investigated the involvement of E93 in female neoteny by cloning XvE93. Interestingly, while we detected a clear up-regulation of XvE93 expression in pupal and adult stages of males, persistent low levels of XvE93 were detected in X. vesparum females. However, a specific up-regulation of XvE93 was observed in the cephalothorax of late 4th female instar larva, which correlates with the occurrence of neotenic-specific features in the anterior part of the female body. Moreover, the same expression dynamic in the cephalothorax and abdomen was also observed for other two critical metamorphic regulators, the anti-metamorphic XvKr-h1 and the pupal specifier XvBr-C. The specific up-regulation of XvE93 and XvBr-C in the female cephalothorax seems to be the result of an increase in 20-hydroxyecdysone (20E) signaling in this region for we detected higher expression levels of the 20E-dependent nuclear receptors XvHR3 and XvE75 in the cephalothorax. Overall, our results detect a sex-specific expression pattern of critical metamorphic genes in X. vesparum, suggesting that neoteny in Strepsiptera results from the modification of the normal expression of E93, Br-C and Kr-h1 genes.